(untitled) (Global Journal of Science Frontier Research, 2021)
Annotation-Crop production is one of the dynamically developing branches of agriculture. The main directions of the industry’s development are not only to increasecrop yields but also to obtain environmentally friendly products. The work presents the rationale for the use of laser light to activate the growth of plants. The example of Savoy cabbage shows the positive effect of using a semiconductor laser with a wavelength of 650 nm,radiation power of 150 MW, and a radiation duration of 30 seconds. It shows not only the increase of leaf area by 67% and the head weight by more than 15% but also the accumulation of proteins and carbohydrates by an average of 15% in the plant samples of the experimental group. All this indicates an increase in the energy of plant growth. The proposed technology makes it possible to increase the yield of crop production with minimal usage of fertilizers and chemical protection products.